Interleukin-1β and interleukin-1receptor antagonist polymorphisms in Egyptian children with febrile seizures: A case-control study. Issue 11 (March 2017) - Al Morshedy, Salah; Elsaadany, Hosam F.; Ibrahim, Hany E.; Sherif, Ashraf M.; Farghaly, Mohsen A.A.; Allah, Mayy A.N.; Abouzeid, Heba; Elashkar, Shaimaa S.A.; Hamed, Mohammed E.; Fathy, Manar M.; Khalil, Atef M.; Noah, Maha A.; et al.
Abstract : Abstract: Febrile seizure is the most common seizure disorder of childhood. Of the pro-inflammatory cytokines, interleukin-1 is defined as the first endogenous pyrogen. We designed this study to investigate single-nucleotide polymorphisms (SNPs) situated at positions –31 (C/T), and –511 (C/T) of interleukin-1beta (IL-1β) gene promoter and interleukin-1receptor antagonist (IL-1RA) gene variable number of tandem repeats in intron 2 (VNTR); to determine whether these polymorphisms could be a marker of susceptibility to febrile seizures in Egyptian children and we also measured the serum level of IL-1β to assess its relation to such polymorphisms. This was a case-control study included 155 patients with febrile seizure, and matched with age, sex, ethnicity 155 healthy control subjects. IL-1β promoter at positions −31 (C/T), −511 (C/T), and IL-1RA gene VNTR polymorphisms were genotyped by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), while the serum IL-1β levels were measured by enzyme-linked immunosorbent assay (ELISA) method. The frequency of the IL-1β-511 TT genotype and T allele at the same position were observed to be increased in patients with febrile seizures (FS) compared with the control group (odds ratio [OR]: 3.96; 95% confidence interval [CI]: 1.68–9.5; P = 0.001 for the TT genotype and OR: 1.65; 95% CI: 1.18–2.3; P = 0.003 for the T allele, respectively). The IL-1 RA II/II homozygous variant and IL-1 RA allele II were overrepresented in patients with FS than control group (OR: 4.02; 95% CI: 1.78–9.15; P = 0.001and OR: 1.73; 95% CI: 1.24–2.4; P = 0.001, respectively). We found a significant positive association between the IL-1 RA II/II genotype and susceptibility to FS in sporadic cases as did allele II at the same position (OR: 5.04; 95% CI: 2.1–12.5 for the IL-1 RA II/II genotype; P = 0.001) and (OR: 1.94; 95% CI: 1.3–2.8 for the allele II; P = 0.001, respectively). Carriers of the IL-1RA II/II homozygous variant and allele II had significantly higher serum levels of IL-1β compared with those with other genotypes and alleles. We demonstrate for the first time that the presence of a T allele or TT genotype at -511 of IL-1β promoter and IL-1RA II/II genotype constitute risk factors for developing FS in Egyptian children.